Evaluation of Clinical Consequences of Dental Caries in Autistic Children in Isfahan Special Centers Based on pufa/PUFA index - Narjes Amrollahi; Rasoul Amouchi (Mashhad University of Medical Sciences, 2021)
Introduction:Autism is a congenital neurological disorder characterized by impaired social interaction, communication, and behavior. Due to the special condition of these children and their inability to observe oral hygiene, patients depend on their caregivers. In this regard, the present study aimed to evaluate the clinical consequences of untreated dental caries based on the pufa/PUFA index in autistic children aged 6-12 years old In Isfahan. Materials and Methods: This descriptive-analytical study was conducted on 90 children in autistic centers based on clinical examination. The examination was performed using a mirror, explores, and headlight. The pufa/PUFA checklist and severity of the autism were documented for each child. The data were analyzed in SPSS software using the Mann-Whitney U test. Results: The majority of children had mild autism. The mean of pufa and PUFA indices in the autistic children were obtained at 3.43±2.46 and 0.62±0.29, respectively. Among all the pufa/PUFA index parameters, the exposed pulp) was higher. In the current study, there was no significant difference between males and females in terms of autism severity (P=0.205). Moreover, the autism severity had no significant relationship with pufa/PUFA index in deciduous and permanent teeth (P>0.05). Conclusion: The results of the current study pointed out that the rate of caries was relatively high in autistic children, and oral hygiene in primary dentition was worse than permanent dentition.